(untitled) (Mustansiria Dental Journal, 2019)
Background: Root caries is considered as a major dental problem in persons with advanced age. It most often occurs at or close to the cemento-enamel junction. A dominating dental problem in the patients of periodontal diseases is the root caries. Specifically, gingival recession often results in root surfaces exposure and increase risk for root caries. The aim from this study is to determine the prevalence of the gingival recession and the root caries depth, and to find the relationship between root caries depth and gingival recession at different age stages for both genders using scores for both root caries depth and gingival recession. Materials and Methods: The study sample consisted of (144) patients was selected, aged (21-65) years old, from patients attending the Dental Clinics of Al-Mustansiriyah University, Alrafidain College and Althawra Dental Centers. Questionnaire case sheet forms were filled by dentist. For each patient, clinical examination was performed using a periodontal probe to measure root caries depth and gingival recession. Results: The prevalence of gingival recession and root caries was higher in male groups (1,3,5) in comparison with female groups (2,4,6) and increased with age in all teeth and surfaces. The study showed that females aged 21-35 years (group 2) had lower percentage of gingival recession (8% for teeth and 5.1% for surfaces) and root caries (6.9% for teeth and 5.3% for surfaces); while males aged 51-65 years (group 5) showed higher percentage of gingival recession (23.7% for teeth and 24.8% for surfaces) and root caries (30.6% for teeth and 25.3% for surfaces). Mandibular anterior teeth exhibited more gingival recession (22.1) than other teeth; while mandibular molar teeth exhibited more root caries (23.6%) than other teeth. The facial surfaces of maxillary and mandibular teeth were showed higher percentage of gingival recession (15.3% for maxillary, 17.2% for mandibular) and root caries (17.3% for maxillary, 20.5% for mandibular) in comparison with other surfaces. This study showed a significant difference between root caries depth scores (1,2,3), gingival recession scores (2,3) and also with the age; while there was non-significant difference between root caries depth scores (1,2,3) and gingival recession score (1). Conclusion: There was a positive relationship between root caries depth and gingival recession with advance of age. This can be related to that, patients with advance of age have susceptibility to expose for longer time to risk factors due to periodontal diseases that can lead to increased gingival recession and root caries. Gingival recession and root caries were found in males more than females.